Pendampingan Pemetaan Manajemen Resiko Pengelolaan Pasar Rakyat di Kabupaten Sidoarjo - Sri Setyo Iriani; Dian Anita Nuswantara; Sanaji (Inspirasi Nusantara, 2021)
The development of more and more modern markets makes it a challenge for the existence of the people's market. The conditions of modern market services that are clean, fast and the variety of product variants greatly affect the income of the people's market traders are indeed very different, but there is a unique value of bargaining and emotional interaction in the people's market that cannot be found in the modern market. Improving people's market services in Sidoarjo is the government's goal because the market is one of the pillars of the economy of the people in Sidoarjo which currently has 19 locations of people's markets with 14,802 traders. To make a people's market with standardized services, it is necessary to have a mapping of market management risks originating from consumers and managers. Therefore, the Universitas Negeri Surabaya's PKM team assisted market managers in Sidoarjo to map out all the risks in the market. From the identification results, there are 21 types of risk grouped into 5 severe risks, 10 moderate risks, and 6 mild risks. Risk classification is based on the magnitude of the impact caused. Knowing the risks from the start is very useful as a basis for determining risk management strategies which will subsequently have an impact on a safe and comfortable market environment for traders, buyers, and market managers.